Politics of Movement: Exploring Passage Points in Responses to COVID-19 and the Plague in the Fifteenth-Century Netherlands - Janna Coomans; Claire Weeda (Journal for the History of Environment and Society)
Engaging the concepts of flow, circulation and blockage can help us to understand the trajectories of pandemics and the social responses to them. Central to the analysis is the concept of obligatory passage points through which networks must pass. Attempts by various actors to control the movement through them, be they government authorities, health experts and caregivers, economic producers or consumers, can create social tensions. Such tensions were duly recognised during the recurring outbreaks of the plague in the Second Plague Pandemic between the fourteenth and the seventeenth centuries. Analysing historical plague ordinances allows us to expose the power mechanisms impacting networks as they move through spaces, and to remain critical of how circulation is controlled and moralised. We argue that historians can contribute to reviewing these mechanisms behind the spread of epidemics and the responses to them from the perspective of movement and blockage.